2017
DOI: 10.1177/2045893217695567
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pediatric pulmonary hypertension trials registered on ClinicalTrials.gov

Abstract: The investigation of pediatric pulmonary hypertension (PH) drugs has been identified as a high priority by the United States National Institutes of Health (NIH). Studying pediatric PH is challenging due to the rare and heterogeneous nature of the disease. We sought to define the pediatric PH clinical trials landscape, to evaluate areas of trial success or failure, and to identify potential obstacles to the study of pediatric PH drugs. Interventional pediatric (ages 0–17 years) PH trials registered on ClinicalT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…However, we found similar rates of noncompletion and nonpublication among pediatric and adult studies. The pediatric trial discontinuation rate of 30% in our study is comparable with prior studies demonstrating noncompletion among 18% to 40% of trials in pediatric populations [10,20,25,26]. The nonpublication rate of 24% for rare disease trials was slightly lower than previously reported rates of 30% to 37% among various cohorts of pediatric trials and may reflect improvements in this practice over time [10,20,25,26].…”
Section: Discussionsupporting
confidence: 83%
“…However, we found similar rates of noncompletion and nonpublication among pediatric and adult studies. The pediatric trial discontinuation rate of 30% in our study is comparable with prior studies demonstrating noncompletion among 18% to 40% of trials in pediatric populations [10,20,25,26]. The nonpublication rate of 24% for rare disease trials was slightly lower than previously reported rates of 30% to 37% among various cohorts of pediatric trials and may reflect improvements in this practice over time [10,20,25,26].…”
Section: Discussionsupporting
confidence: 83%
“…In 2012, a study by Pasquali et al found that an assessment of the clinical trial site data set could describe the overall mix of clinical trials related to children in the United States, which was previously impossible [12]. Afterwards, descriptive analyses of clinical registration trial characteristics for different pediatric diseases began to emerge [13][14][15]. The development of pediatric clinical studies and regulations on registration of ClinicalTrials.gov had offered the opportunity to characterize the landscape of pediatric studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there remains the need for creative trial designs to overcome the difficulties of studying rare and heterogeneous patient population and for long‐term continuation of blinded dose‐ranging for adverse event surveillance 47 . More robust pediatric pharmacokinetic and safety data are also required.…”
Section: Discussionmentioning
confidence: 99%